Peningkatan Kemampuan Penyusunan Instrumen Evaluasi Berbasis Hots Bagi Guru (SMAN 05 Tinggi Moncong) - Netti Herawati; Muhammad Anwar; Ahmad Fudhai (DEDIKASI, 2020)
The implementation of this Community Parthnership Program, PkM aims to improve the understanding of SMAN Negeri 05 Tinggi Moncong teachers about the principles and steps of developing HOTS-based evaluation instruments, the format and components of HOTS-based evaluation instruments, and skilled in preparing HOTSbased evaluation instruments, with a minimum target of 90% of participants of PkM training is able to prepare evaluation instruments well. The implementation of this  activity involved three lecturers from the Department of Chemistry, Faculty of Mathematics and Natural Sciences, Makassar State University, with a background in chemistry and chemistry education. The method applied in the implementation of this PkM is by applying various methods of presentation or lectures, question and answer, discussion, and practice / performance. Then it was continued as an independent assignment outside the classroom for 5 days. All of these activities were carried out online due to the COVID 19 pandemic conditions. This activity succeeded in improving the ability of SMA 05 Tinggi Moncong teachers in developing HOTS-based evaluation instruments